Pengaruh Gaya Kepemimpinan, Sistem Informasi dan Standar Akuntansi Pemerintah terhadap Kinerja Organisasi pada Pemerintah Kota Bima - R . Ayu Ida Aryani; Isra Dewi Kuntary Ibrahim; Muhammd Israfil (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
This research is done to find out the effect of leadership style, accounting information system and government accounting standard on government organizational performance of Bima City. It is applied to 31 regional work units (SKPD) in Bima City by taking the object of echelon II, II and IV echelon officials. This study uses a descriptive method with a quantitative approach. The type of data used is primary data obtained from distributing questionnaires to research respondents. There were 89 of questionnaires carried out and 80 questionnaires were analyzed. Data analysis is using multiple linear regressions with SPSS V.20. Based on the results of the t-test data analysis test, it shows that the leadership style variable has a significant positive effect on the government organizational performance of Bima City with a t-count value (3.746) > t-table (1.991), the accounting information system variable has a positive significant effect on the government organizational performance of Bima City. with a t-count value (3.322) > t-table (1.991) while the accounting standard variable has no significant effect on government organizational performance of Bima City with a t-count value (1.446) < t-table (1.991). Based on the results of the F test, it shows that leadership style, accounting information systems and accounting standards simultaneously have a significant effect on the government organizational performance of Bima City.